Comparative efficacy of Chinese herbal injections for septic shock: A protocol for systematic review and network meta-analysis. Issue 5 (4th February 2022) - Huang, Peiying; Chen, Yan; Liu, Qiang; Lei, Sisi; Feng, Yuchao; Wu, Qihua; Zhang, Haobo; Chen, Bojun; Zeng, Zhongyi
Abstract: Background: Septic shock is a life-threatening syndrome. Despite Western medicine guidelines being continually updated on septic shock, the disease still has a high mortality rate. Chinese herbal injections (CHIs) are injections made from effective components of traditional Chinese medicine, which have a potential therapeutic effect on septic shock and are recommended as the adjunctive treatment for septic shock in China. Although pairwise meta-analysis has been published for category-single CHIs about treatment effects of septic shock, there is no meta-analysis comparing more than 3 various types of CHIs used for septic shock. Methods: Chinese and English databases will be retrieved for randomized controlled trials from the establishment of the databases to September 30, 2021. Two reviewers will perform literature searches and data extractions while another 2 reviewers for risk assessments. RevMan V.5.4 software, Stata V.14.0 software, and R V. 4.1.1 software will be applied to perform pairwise meta-analysis and network meta-analysis. We will apply the Cochrane risk of bias tool to assess the risk of bias while the Grades of Recommendation, Assessment, Development, and Evaluation approach will be used to summarize the results of the study. The PRISMA-P guideline was followed for this protocol. Results: The current study will explore the therapeutic effect of CHIs in the treatment of septic shock through pairwise meta-analysis and network meta-analysis. Conclusion: This study will seek out the best-performed CHIs under various indicators for septic shock, providing supporting evidence for clinical selection of CHIs for septic shock.